KONSTRUKSI REALITAS PEMBERLAKUAN PERDA SYARIAH OLEH KORAN THE JAKARTA POST - Azmi, Alia (Humanus, 2012)
This research aims to analyse the construction of reality on sharia bylaws in the English newspaper The Jakarta Post. The Jakarta Post is currently the biggest national English newspaper with readership includes educated middle class and high-end as well as foreign audience, making its role siginificant in representing news of Indonesia abroad. This qualitative research uses descriptive design and framing analysis to analyse the framing of news about the implementation of sharia bylaws by The Jakarta Post. The research concludes that The Jakarta Post frames sharia bylaws as controversial and incompatible with the legal system and the plural society of Indonesia. The construction of reality is influenced by its pluralist and secularist ideology. Key words: construction of reality, The Jakarta Post, sharia baylaws, pluralist